2019
DOI: 10.1016/j.molliq.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of leaf-based adsorbents for dyes removal: A review

Abstract: The presence of organic dyes in the aquatic environment is a serious global problem because of the serious negative consequences on the quality of ecosystems. Among various physico-chemical methods, the adsorption could be considered a promising alternative for removing dyes from aqueous media, due to its efficiency, high selectivity, low cost, ease of operation, simplicity, and availability in a wide range of experimental conditions. However, all these advantages are closely related to the nature of adsorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
146
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(150 citation statements)
references
References 127 publications
(137 reference statements)
1
146
0
3
Order By: Relevance
“…Consequences of rapid growth include environmental disturbances and pollution problems. In addition to other needs, water demand for industry has increased rapidly and resulted in the generation of a large amount of wastewater containing large amounts of pollutants [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequences of rapid growth include environmental disturbances and pollution problems. In addition to other needs, water demand for industry has increased rapidly and resulted in the generation of a large amount of wastewater containing large amounts of pollutants [1].…”
Section: Introductionmentioning
confidence: 99%
“…Water body pollution by dyes may be toxic to aquatic organisms, be resistant to natural biological degradation [1], and cause changes in biological cycles. They also pose risks to human health, as studies show that some of these products can be carcinogenic or mutagenic, and cause allergies, dermatitis, and skin irritation [4].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with other adsorbents indicated a high metal ion adsorption capacity of nano kaolinite extracted and prepared from deposits of Sweileh sand, west Amman, Jordan. Findings revealed that nano kaolinite offered promising adsorption efficiency versus various other adsorbents reported for metal ions adsorption and nano kaolinite could possibly be used for the adsorption of heavy metal ions from industrial effluents (Bulgariu et al, 2019;Chen et al, 2019;Gaikwad et al, 2010;Godiya et al, 2019a;Godiya et al, 2019b;Ibrahim and Fakhre, 2019;Jiang et al, 2019;Kausar et al, 2018a;Kausar et al, 2018b;Khera et al, 2019;Liang et al, 2013;Mousavi et al, 2019;Nadeem et al, 2016;Sandoval et al, 2019;Zafar et al, 2018;Zhao et al, 2019).…”
Section: Comparison Of Nano Kaolinite With Other Adsorbentsmentioning
confidence: 99%
“…Activated carbon has been the most widely used adsorbent in water and wastewater treatment, but its use has some major drawbacks resulting from its high production cost and the need for regeneration accompanied by management of resulting sludge [8]. ere is therefore the need worldwide for low-cost adsorbents such as clay [8], Musa paradisiaca and Ipomoea batatas peels [9,10], leaf-based adsorbents [11], and modified chitosan [12] for heavy metals and other contaminants adsorption from water and wastewater. ere is particularly an increasing trend towards the use of waste biomass materials as adsorbents for heavy metal removal from water and wastewater because of their abundant availability and low cost, with relatively high fixed carbon, presence of porous structure, and high content in cellulose, lignin, hemicellulose, etc.…”
Section: Introductionmentioning
confidence: 99%
“…with good functional groups that can bind heavy metals [7,13,14]. Researchers are showing growing interest on adsorbents from leaf-based materials (in raw or modified from) because they are cheap and available in all parts of the world in very large quantities with very little use [11]. ey contain hydroxyl, carboxyl, carbonyl, amino, and nitro groups which can serve as binding sites for pollutants during adsorption.…”
Section: Introductionmentioning
confidence: 99%